Periodontal inflamed surface area in patients on haemodialysis and peritoneal dialysis: a Croatian cross-sectional study - Bojana Križan Smojver; Karmela Altabas; Mladen Knotek; Nikolina Bašić Jukić; Andrej Aurer (BMC, 2020)
Abstract Background The decision to initiate dialysis treatment via haemodialysis (HD) or peritoneal dialysis (PD) often involves the consideration of complex factors and remains a matter of debate. The purpose of this study was to quantify the inflammatory burden that periodontitis causes in dialysis patients and to examine whether patients on PD and HD differ in terms of the periodontal inflamed surface area (PISA), which can be helpful for selecting the most appropriate dialysis modality. Methods A cross-sectional study was performed on 58 consecutive patients on HD and 31 consecutive patients on PD. PISA was calculated using measurements of the clinical attachment level, recession and bleeding on probing. We performed the primary analysis using multivariable robust regression. Results Patients on PD had a 746 mm2 (93%) lower mean PISA than patients on HD after adjustment for 20 possible confounders, including the duration of dialysis. The type of dialysis was independently correlated with the PISA (semipartial correlation: − 0.50; p = 0.017; false discovery rate < 5%). After adjusting for confounding factors, the correlation between the duration and type of dialysis was not significant (F (2,44) = 0.01; p = 0.994; η2 = 0.00). Differences in the PISA between patients who had undergone dialysis for less than a year, 2-3 years or ≥ 3 years were not significantly different in either of the two dialysis groups. Conclusions PISA levels in Croatian patients on dialysis indicate a high need for periodontal treatment. PD is associated with a smaller PISA independent of many sociodemographic, lifestyle, laboratory and clinical factors. The duration of dialysis does not influence PISA levels. Trial registration ISRCTN17887630 . A clinical study to investigate gum infection in patients undergoing kidney dialysis.